(untitled) (Acta Education, 2023)
The aggregation processes of NiO nanoparticles have been studied to some extent in ideal environments, i.e., gas and aqueous solutions, but their interaction mechanisms between aqueous media and nanoclusters are still not fully understood. In this work, the environmental effect on the aggregation process of NiO nanoclusters with a size of about 1 nm has been studied using molecular dynamics simulations. Obtained results show that (1) nanoclusters are located at a longer distance from each other in aqueous media in comparison to vacuum due to the hydrodynamic shell (with a thickness of 0.08 nm) formed around the NiO nanoaggregates affected by the aqueous environment, and (2) the stability of NiO nanoclusters in the water environment decreases as a result of the formation of the hydrodynamic shell. Overall, these results suggest that a better understanding of the tuning of nanocatalyst size will lead to the selective synthesis of nanomaterials with unique properties, which are the basis of nanotechnology.